2009
DOI: 10.1016/j.peptides.2009.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1 protects mesenteric endothelium from injury during inflammation

Abstract: Glucagon-like peptide-1 (GLP-1) is a proglucagon-derived hormone with cellular protective actions. We hypothesized that GLP-1 would protect the endothelium from injury during inflammation. Our aims were to determine the: (1) effect of GLP-1 on basal microvascular permeability, (2) effect of GLP-1 on increased microvascular permeability induced by lipopolysaccaride (LPS), (3) involvement of the GLP-1 receptor in GLP-1 activity, and (4) involvement of the cAMP/PKA pathway in GLP-1 activity. Microvascular permeab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…Experimental evidence suggests beneficial effects of GLP-1 during sepsis, with reduced mortality being found in endotoxin-challenged DPP-4 knockout rats and activation of the GLP-1 receptor improving prognosis in the same model (39). Mechanistically this might be mediated by anti-inflammatory capacities of GLP-1, leading to reduced oxidative stress and tissue protection (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence suggests beneficial effects of GLP-1 during sepsis, with reduced mortality being found in endotoxin-challenged DPP-4 knockout rats and activation of the GLP-1 receptor improving prognosis in the same model (39). Mechanistically this might be mediated by anti-inflammatory capacities of GLP-1, leading to reduced oxidative stress and tissue protection (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, sitagliptin might exert anti-inflammatory action in the kidney through GLP-1 receptor by increasing active GLP-1, possibly leading to the reduction of albuminuria. Another anti-inflammatory property of GLP-1 including involvement of the cAMP/PKA pathway might also contribute to reducing albuminuria [8]. It has been reported that treatment with liraglutide resulted in a clinically significant reduction in blood pressure, which could not be fully accounted for by the reduction in body weight [9,10].…”
Section: Conflicts Of Interestsmentioning
confidence: 99%
“…Besides these direct effects on the pancreas, GLP-1 reduces gastric emptying and appetite, improves peripheral glucose uptake, and limits hepatic glucose production, thus also indirectly contributing to glucose homeostasis. Moreover, recent data suggest that GLP-1 has direct effects on endothelial function [2,3], inflammatory cell activation [4] and myocardial function [5]. Furthermore, the stable GLP-1 analogue exendin-4 stimulates the proliferation of human coronary artery endothelial cells in vitro through phosphoinositide 3-kinase/Akt-and endothelial nitric oxide synthasedependent pathways, effects that are shared by both native GLP-1 and its major metabolite GLP-1 [6].…”
Section: Introductionmentioning
confidence: 99%